Effect of Water Stress on Moisture Content Distribution in Soil and Morphological Characters of Two Tomato (Lycopersicon esculentum Mill) Cultivars - Nahar, K.; Ullah, S. M. (Journal of Scientific Research, 2011)
This study investigates the effects of water stress on moisture content distribution at different soil layers (pot) and on morphological characters of tomato plants. Three treatments of moisture level were imposed, viz, 100%, 70% and 40% of the field capacity. Moisture content distribution was higher at the surface and decreased with increasing stress at all growth stages. Yield and related morphological characters responded better at 70% of the field capacity compared with other treatments. Keywords: Tomato; Water stress; Moisture content; Tomato yield; Yield component. © 2011 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi:10.3329/jsr.v3i3.7000 J. Sci. Res. 3 (3), 677-682 (2011)